Long-Term Safety and Effectiveness of Canakinumab in Patients with MKD/HIDS: Interim Analysis of the RELIANCE Registry - Prasad T. Oommen; Tilmann Kallinich; Juergen Rech; Norbert Blank; Julia Weber-Arden; Jasmin B. Kuemmerle-Deschner (Rheumatology and Therapy)
Abstract Introduction Interim analysis of the long-term safety and effectiveness of canakinumab, at a patient level, in the mevalonate kinase deficiency/hyperimmunoglobulin-D syndrome (MKD/HIDS) cohort of the RELIANCE registry. Methods From June 2018, the RELIANCE registry enrolled paediatric (aged ≥ 2 years) and adult patients (aged ≥ 18 years) with MKD/HIDS who were receiving canakinumab as part of their routine medical care. Safety, physician- and patient-reported measures of disease activity and dosing patterns were evaluated at baseline and every 6 months until end-of-study visit. Results At the analysis cut-off date of December 2022, eight patients with MKD/HIDS were enrolled. Five (62.5%) were children (< 18 years) and five (62.5%) were female. The median patient age was 8.0 (range 2.0–39.0) years, and all patients were pre-treated with canakinumab prior to enrolment (median duration of canakinumab treatment: 3.8 years). Canakinumab was well tolerated, with seven (87.5%) patients reporting 48 adverse events (incidence rate/100 patient years: 218.1). No serious adverse drug reactions were reported. Patients continued to receive vaccinations during long-term treatment with canakinumab. Disease activity, evaluated by physician-reported (physician’s global assessment, disease remission, C-reactive protein, serum amyloid A, erythrocyte sedimentation rate) and patient-reported (autoinflammatory disease activity index diary, disease activity, fatigue, impact on social life) measures, was generally well controlled throughout the study. Over 50.0% of patients maintained disease remission from baseline to month 24, and medians of all inflammatory markers remained within normal limits throughout the study. Most patients received higher than the recommended starting dose of canakinumab throughout the study. Conclusion Data from this interim analysis of a unique registry of patients with a rare disease support the long-term safety and effectiveness of the IL-1-blocking agent canakinumab for the treatment of MKD/HIDS.